(untitled) (International Journal of Food and Nutritional Sciences, 2021)
A derivative of isatin, a flexible scaffold with a wide range of biological functions in medicinal chemistry, is isatin-3-thiosemicarbazone (ISTSC). With an emphasis on ISTSC’s synthesis, chemical characteristics, biological activities, and possible pharmaceutical uses, this research attempts to provide a thorough analysis of the substance. The mechanisms of action, structure-activity connections, and prospects for further development of ISTSC as a therapeutic agent are also highlighted in the review. A flexible scaffold in medicinal chemistry, isatin is the source of isatin-3-thiosemicarbazone (ISTSC), which has been shown to have a wide range of important biological properties. The wide range of therapeutic potentials of ISTSC is attributed to its unique chemical structure, which consists of an isatin moiety conjugated with a thiosemicarbazone group. The objective of this research is to provide a thorough analysis of ISTSC, including its synthesis techniques, specific chemical characteristics, and a thorough investigation of its biological activities. Because of its antibacterial, antiviral, anticancer, and anti-inflammatory properties, ISTSC is a molecule that is very desirable for use in drug development. The review explores how ISTSC interacts at the molecular level with different biological targets, delving into the mechanisms of action that underlie these biological activities.